Mechanization Bundle Report: Service provider model for CLIMATE-SMART Mechanization of smallholder farmers in Zambia - Matin, M. A.; Mulundu, S; Zingwari, O (2025)
Conservation agriculture (CA) based mechanization is receiving better recognition as a sustainable solution to improve land and labour productivity and help meet the rising global food demand under the changing climate. In Zambia, the adoption of mechanization is crucial for the smallholder farmers to improve their productivity, increase income, mitigate peak-season labour crisis, and reduce drudgery and post-harvest losses. The report outlines the steps towards empowering farmers to become mechanization service providers (SPs) in the farming communities and help them access mechanization services for a fee. The project activities included machinery needs assessment, awareness creation, screening and selection of the farmers to become mechanization service providers, providing technical and business training to the SPs, mechanics, and operators. Three SPs were established, two in Chongwe district and one in Chibombo district. The SPs were provided with starter pack machinery consisting of a two-wheel tractor, a double-row ripper, a no-till multi-crop planter, a maize sheller, a multi-crop thresher, and a trailer. Following the training in technical and business development skills, these SPs established mechanization demonstration plots to showcase climate-smart agricultural mechanization technologies and create demand for his/her service in the communities. Data collected from these initiatives indicated significant outreach, with hundreds of smallholder farmers accessing mechanization services, thereby creating demand and the SPs generating a net income of up to $11.71 per day. The report highlights the profitability of services such as maize shelling and transportation, which have adapted to market dynamics through competitive pricing. Overall, the findings underscore the transformative impact of mechanization and the service provider model in fostering sustainable agricultural mechanization for climate-smart agriculture, creating income opportunities, and bolstering rural economies in Zambia.